Mutagenic Effects of Gamma Rays and EMS on Frequency and Spectrum of Chlorophyll Mutations in Pea (Pisum sativum L.) - Dhale3; R.A. Satpute4, G.S. Dhulgande1, D.S. Ghogare2, D.A. (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">The mutagenic effect of gamma rays (5kR, 7kR and 10kR) and ethyl methanesulphonate (0.05%, 0.10% and 0.15%) on frequency and spectrum of chlorophyll mutations in two varieties of pea, namely, DDR-53 and DMR-55 have been observed. Conclusively the various doses or concentrations of mutagenic treatments have independent response towards frequency and spectrum of chlorophyll mutations.